Employees' understanding of corporate responsibility and Kesko's CSR principles - Salomaa, Jenni (2016)
Participating in corporate social responsibility (CSR) activities can be beneficial for companies in a myriad of ways, not the least by building and maintaining a flourishing employee-company relationship. CSR can increase employee motivation and job satisfaction, employees may experience higher organizational commitment as a result of CSR, and CSR can improve employees’ positive self-images via company identification. However, companies often fail to harness the benefits CSR can bring due to insufficient employee education and employee involvement in the planning phase of CSR projects. This Master’s Thesis aims at examining how K-Retailer employees understand the broad concept of CSR and how they perceive Kesko’s CSR approach. Using typing to analyse primary data collected from eight employee interviews through discretionary sampling, this qualitative empirical case study inductively formed five employee types according to employees’ understanding of CSR, namely advocates of environment, socially concerned, economically effective, ethically aware and uncertain. The research findings suggest that the understanding of the concept of CSR varies greatly among average K-Retailer employees, and that most K-Retailer employees have a vague or no perception of Kesko’s CSR activities. The findings further propose that even if an employee would show an interest or knowledge in CSR issues in general, this does not necessarily translate into knowledge about the specific CSR issues of their employer. This research contributes to the academic literature of employee-company relationship and CSR, and it provides value to Kesko through managerial implications, such as adopting a bottom-up approach to CSR and increasing the proximity and engagement of their employees in CSR activities by involving them in the planning of new CSR programmes. Future research could investigate employee evolution from one type to next due to increased CSR education.